The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/acp-13-10461-2013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of air quality over southwestern Ontario: main findings from the Border Air Quality and Meteorology Study

Abstract: Abstract. This paper serves as an overview and discusses the main findings from the Border Air Quality and Meteorology Study (BAQS-Met) in southwestern Ontario in 2007. This region is dominated by the Great Lakes, shares borders with the United States and consistently experiences the highest ozone (O 3 ) and fine particulate matter concentrations in Canada. The purpose of BAQS-Met was to improve our understanding of how lake-driven meteorology impacts air quality in the region, and to improve models used for f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 72 publications
(139 reference statements)
0
25
0
Order By: Relevance
“…high pollution events due to lake breeze circulation (Foley et al, 2011). Coastal regions in the United States where this phenomenon has been observed include Lake Michigan (Dye et al, 1995), Lake Erie (Brook et al, 2013), the Gulf of Mexico (Mazzuca et al, 2016), and the Chesapeake Bay (Loughner et al, 2014;Stauffer & Thompson, 2012;Sullivan et al, 2019). There is still significant uncertainty regarding the conditions driving coastal O 3 production, which limits confidence in proposed emission control strategies for reducing O 3 exceedances in such regions.…”
mentioning
confidence: 99%
“…high pollution events due to lake breeze circulation (Foley et al, 2011). Coastal regions in the United States where this phenomenon has been observed include Lake Michigan (Dye et al, 1995), Lake Erie (Brook et al, 2013), the Gulf of Mexico (Mazzuca et al, 2016), and the Chesapeake Bay (Loughner et al, 2014;Stauffer & Thompson, 2012;Sullivan et al, 2019). There is still significant uncertainty regarding the conditions driving coastal O 3 production, which limits confidence in proposed emission control strategies for reducing O 3 exceedances in such regions.…”
mentioning
confidence: 99%
“…The calibration of vehicle-based measurements is important for integration with stationary measurements and with mobile measurements from differing vehicle platforms. Studies evaluating the trends in near-surface ocean winds demonstrated that systematic bias in measurement methods contributed to an increasing trend in global wind speed in reported climate data (Cardone et al, 1990;Ramage, 1987;Peterson and Hasse, 1987). The International Comprehensive Ocean Atmosphere Data Set (ICOADS) documents wind measurements from Voluntary Observing Ships (VOSs) and other marine platforms (Thomas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The datasets date back prior to the 1940s and provide data for observed changes in climate patterns (Ramage, 1987). The datasets have been studied extensively to explain the increasing trend in global wind speed after the 1940s (Cardone et al, 1990), when archived data prior to the 1940s showed a decreasing trend (Thomas et al, 2008). Peterson and Hasse (1987) and Ramage (1987) attributed the shift from decreasing to increasing wind speed to the change in the method of reporting ship-based wind measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ontario, meteorology is affected primarily by the midlatitude westerly jet and the eastward progression of cyclones, anticyclones, and fronts across eastern North America, and significant modification by the three Great Lakes surrounding southern Ontario often affects local weather and air quality [34]. Local air pollutant concentrations are mainly determined by the combination of emissions, chemistry and local meteorology, but an estimated 55% of air pollution impacts result from transboundary flow of emissions from the United States [35].…”
Section: Introductionmentioning
confidence: 99%